Give Thank You a Try - Patterson, James 1947- (New York : Little, Brown and Company, 2017)
An illustrated exploration of the phrase "thank you" and the many scenarios of kindness and gratitude in which it can be used.
Keywords: Gratitude -- Juvenile fiction; Gratitude -- Fiction